Parental child abduction in Malaysia and Nigeria: an overview - Che Soh @ Yusoff, Roslina; Abdul Hak, Nora; Alkali, Alhaji Umar (Faculty of Law, Accountancy and International Relations, UniSZA, 2015)
Abduction often involves the parents of the child. After a marriage is dissolved most parents will want to have custody of the children. The party that is unable to lawfully obtain custody of children sometimes resort to abduction. Abduction of children is an issue that raises concern due to its effect on the child. Abducted children are sometimes even taken outside the country of abduction to another country by the non-custodian parent in order to prevent tracing and punishment. These attributes of abduction have a far reaching negative consequence on the child. The sudden separation of the child with his environment and the attempt to hide the child negatively affects the child physically and psychologically. Though there is no specific provision on parental abduction, the Malaysian and Nigerian laws prohibit child abduction generally and prescribe punishment for the crime. The paper examines the position of parental child abduction under the Malaysian and Nigerian laws and the approach of the courts in dealing with the matter. The paper also briefly discusses the position of child abduction under Islamic law and suggests ways through which much protection will be provided to children against parental child abduction. Doctrinal methodology is used in the paper in arriving at the findings of the work.